Modeling and structuring design rationale to enable knowledge reuse. Issue 3 (7th October 2019) - Siddharth, L.; Chakrabarti, Amaresh; Ranganath, R.
Abstract: We aim to lend insights into "what" constitutes design rationale and "how" to capture these. We restrict the scope of design rationale to the cases of failures observed while testing real engineered systems. We propose a model as an integration of a system hierarchy, a causal chain, and a causality model to cast multiple views of design rationale. The model is structured into databases using a newly introduced version of design structure matrices and supported using a web interface called CRIS 4 P, which is deployed at a space agency. We report a case example from the spacecraft domain and benchmark the proposed model against IBIS‐FAD model.